Distinct Aeromonas Populations in Water Column and Associated with Copepods from Estuarine Environment (Seine, France) - Chaix, Gautier; Roger, Frédéric; Berthe, Thierry; Lamy, Brigitte; Jumas-Bilak, Estelle; Lafite, Robert; Forget-Leray, Joëlle; Petit, Fabienne (Frontiers in Microbiology, 2017)
Aeromonas spp. are ubiquitous bacteria primarily recovered from aquatic ecosystems. They are found in fresh water as well as estuarine and marine waters, and in association with numerous autochthonous aquatic organisms in these environments. However, aeromonads are also etiologic agents of fish diseases and are now recognized as emerging pathogens in humans. The estuary is therefore a key environment, harboring autochthonous aeromonads, and aeromonads originating from humans and animals, mainly released by treated WWTP effluent or watershed run-off via tributaries. The present study compares the abundance and the diversity of Aeromonas populations. Over 2 years of monitoring (eight campaigns from February 2013 to November 2015), the occurrence of Aeromonas was investigated within the water column (water and fluid mud) and in association with copepods. Moreover, the diversity of Aeromonas populations was ascertained by analyzing gyrB and radA sequences, and the antibiotic-resistance phenotypes were determined using the disc diffusion method. This study shows, for the first time, the presence of Aeromonas spp. in water (1.1 × 102 to 1.2 ± 0.3 × 103 CFU.100 mL-1), fluid mud (2.6 ± 2.6 × 102 to 9.8 ± 0.9 × 103 CFU.g-1) and in association with living copepods (1.9 ± 0.7 × 102 to > 1.1 × 104 CFU.g-1) in the Seine estuary. Moreover, the diversity study, conducted on 36 strains isolated from the water column and 47 strains isolated from copepods, indicates distinct populations within these two compartments. Strains distributed in five clusters corresponding to A. bestiarum (n = 6; 5.45%), A. encheleia (n = 1; 0.91%), A. media (n = 22; 20.0%), A. rivipollensis (n = 34; 30.91%) and A. salmonicida (n = 47; 42.73%). A. salmonicida is the most abundant species associated with E. affinis (n = 35; 74.47%). In contrast, A. salmonicida accounts for only 30.56% (n = 11) of isolates in the water column. This study shows the coexistence of distinct populations of Aeromonas in the oligohaline area of an anthropized estuary. Moreover, A. media, a putative human pathogen, present in the water column and abundant in the WWTP samples, was not detected in association with living copepods.